Effect of Nitrogen and Sulphur Levels on Growth, Yield and Quality of Seed in Radish (Raphanus sativus L.) - PRIYA ATAL; SS KUSHWAH; RK SHARMA; BK KACHOULI (Seed Research, 2026)
A field investigation was carried out at Bahadari Farm, Research Block of Department of Vegetable Science, College of Horticulture, Mandsaur (M.P) during 2020-21. Twelve treatments comprised of four levels of nitrogen (N1-60, N2-80, N3-100 and N4-120 kg/ha) and three levels of sulphur S1-15, S2 -30 and S3-45 kg/ha) were laid in factorial randomized block design with three replications. Observations were recorded on plant height at harvest stage, number of branches per plant at harvest stage), fresh weight of shoot at harvest stage, dry weight of shoot at harvest stage, days to 50% flowering, days to 50% maturity, number of siliqua per plant, siliqua length (cm), number of seed per siliqua, siliqua yield per plant (g), seed yield per plant (g), seed yield (q/ha). Quality of radish seed was determined with respect to germination (%), 100 seed weight (g) and seedling vigour index-I. Findings revealed that application of N2S2 (80kg nitrogen +30kg sulphur/ha) resulted in highest seed yield (10.69q/ha). Highest seed germination (91.67%) noted with N3S3 which was at par to N2S3 (90%) and N2S2 (89%).